NATIONAL AND TERRITORIAL APPROACH TO PREPARING YOUNG PEOPLE FOR INDEPENDENT LIFE IN THE PROCESS OF DEVELOPING A CULTURE OF HEALTHY LIFE - Astanakulov Kamoliddin Makhkamovich (Scholar Express Journals, 2022)
This article provides a theoretical basis for the development of mechanisms of ethnic and systemic approach to improving the process of developing a culture of healthy living among young people.
Keywords: Involvement; youth; society; values